2014
DOI: 10.2989/17280583.2014.953955
|View full text |Cite
|
Sign up to set email alerts
|

Use of counselling services by school-attending adolescent girls in Nigeria

Abstract: School authorities will encourage uptake of counselling services by adolescents when adequate counselling consulting rooms are provided. This will increase confidence in adolescent clients and reduce fear attached to use of these services. This will improve their mental health and their academic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Confidentiality is considered as a major factor in the effectiveness and delivery of counselling services. Studies done by Azfredrick (2015), Chan and Quinn, (2012), Jenkins (2010), Wu, et al (2012), Kamunyu, et al, (2015), Mushaandja et al, and Momanyi, (2013), found that lack of confidentiality was one of the major factors inhibiting the use of counselling services by students.…”
Section: Back Ground Of the Studymentioning
confidence: 99%
“…Confidentiality is considered as a major factor in the effectiveness and delivery of counselling services. Studies done by Azfredrick (2015), Chan and Quinn, (2012), Jenkins (2010), Wu, et al (2012), Kamunyu, et al, (2015), Mushaandja et al, and Momanyi, (2013), found that lack of confidentiality was one of the major factors inhibiting the use of counselling services by students.…”
Section: Back Ground Of the Studymentioning
confidence: 99%
“…"Becoming an object": sexual harassment and violence It is on record that significant unconventional sexual behaviours such as rape, sexual harassment and paedophilia are perpetrated against girls by men who see them as sexual objects due to beliefs, culture and socioeconomic grounds (Esiet et al, 2001;Izugbara, 2010;Azfredrick, 2015;Khoja-Moolji, 2015). There are misguided perceptions by some males in relation to sexual maturation with such saying as "when a tree begins to produce ripe fruits it start attracting plucking throws".…”
Section: Ill Health and Inadequate Facilities And Servicesmentioning
confidence: 99%